2012
DOI: 10.1002/hyp.9367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the snow conditions in the major watersheds of Afghanistan using multispectral and passive microwave remote sensing

Abstract: Since the winter season of 2004–2005, annual snow assessments have been conducted for the major watersheds of Afghanistan using multispectral (AVHRR and MODIS) and passive microwave (SSM/I and AMSR‐E) remote sensing technologies. Because of limited ground‐based observations of precipitation and snow pack conditions, remote sensing provides a unique opportunity to assess these conditions at different scales offering an appraisal of current conditions from a historical context. This paper describes the methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
11
2
Order By: Relevance
“…In every basin on 1 April, there were many areas with more reconstructed SWE than the passive microwave saturation limit of 150 mm (Hancock et al, 2013;Kelly et al, 2003;Takala et al, 2011;Tedesco and Narvekar, 2010). Basin wide, differences between the results of this study and the results reported in Daly et al (2012) were small, < 8 mm, for all basins except the Upper Kabul (22 mm difference), which had the highest average SWE in both studies.…”
Section: Validation In Afghanistancontrasting
confidence: 70%
See 3 more Smart Citations
“…In every basin on 1 April, there were many areas with more reconstructed SWE than the passive microwave saturation limit of 150 mm (Hancock et al, 2013;Kelly et al, 2003;Takala et al, 2011;Tedesco and Narvekar, 2010). Basin wide, differences between the results of this study and the results reported in Daly et al (2012) were small, < 8 mm, for all basins except the Upper Kabul (22 mm difference), which had the highest average SWE in both studies.…”
Section: Validation In Afghanistancontrasting
confidence: 70%
“…By basin, NS efficiencies are higher averaging 0.89 and ranging from 0.87-0.91, showing that most of the forecasting challenge occurs year-to-year. Given the lack of water resources monitoring and management in Afghanistan and the high proportion of runoff from snowmelt (Daly et al, 2012;Vuyovich and Jacobs, 2011), our machine learning predictions could improve runoff predictions, which are likely based on mean conditions. Figure 10 shows the predictor performance, ranked by importance, a relative measure ranging from 0 to 1 explained in Sect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have noted that SWE estimates from the Chang equation have high uncertainties (e.g., Kelly et al, 2003;Kelly, 2009;Tedesco and Narvekar, 2010;Daly et al, 2012), particularly in dense forests. However, as much of our study area is non-forested -and we use SWE only as a rough estimate of snow volume -we choose to rely on the simple Chang equation rather than a more complex algorithm for SWE estimation.…”
Section: Datasetsmentioning
confidence: 99%